1976
DOI: 10.1136/jnnp.39.3.221
|View full text |Cite
|
Sign up to set email alerts
|

Changes in CO2 responsiveness and in autoregulation of the cerebral circulation during and after halothane-induced hypotension.

Abstract: SYNOPSIS C02 responsiveness of the cerebral circulation has been measured in baboons before, during, and after halothane-induced hypotension. At a systolic blood pressure (BP) of 60 mmHg, CO2 responsiveness was abolished, but was maintained at higher levels of BP. After hypotension, CO2 responsiveness returned to control values. Autoregulation to BP increases induced by intravenous noradrenaline was impaired when cerebral perfusion pressure during the hypotensive period had been below 30-40 mmHg. It is conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…There have been contradictory data regarding the effects of induced hypotension on cerebrovascular CO 2 reactivity under anesthesia in animal studies and in studies of patients without diabetes mellitus [5,[16][17][18]. Artru and Colley [4] and Artru [5] reported that cerebral vascular responses to hypocapnia during [16] showed the absence of cerebrovascular CO 2 responsiveness after halothaneinduced hypotension at a systolic blood pressure of 60 mmHg in baboons.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There have been contradictory data regarding the effects of induced hypotension on cerebrovascular CO 2 reactivity under anesthesia in animal studies and in studies of patients without diabetes mellitus [5,[16][17][18]. Artru and Colley [4] and Artru [5] reported that cerebral vascular responses to hypocapnia during [16] showed the absence of cerebrovascular CO 2 responsiveness after halothaneinduced hypotension at a systolic blood pressure of 60 mmHg in baboons.…”
Section: Discussionmentioning
confidence: 95%
“…Artru and Colley [4] and Artru [5] reported that cerebral vascular responses to hypocapnia during [16] showed the absence of cerebrovascular CO 2 responsiveness after halothaneinduced hypotension at a systolic blood pressure of 60 mmHg in baboons. Regarding the effects of nicardipine-induced hypotension on cerebrovascular CO 2 reactivity in humans, Kawaguchi et al [6] examined the effects of nicardipine on cerebral vascular responses to hypocapnia (manipulation of the Pa CO 2 level during hypocapnia, 36 ± 1 mmHg), and showed that cerebrovascular CO 2 reactivity was maintained during nicardipine-induced hypotension under fentanyl/diazepam/nitrous oxide anesthesia in patients without diabetes mellitus.…”
Section: Discussionmentioning
confidence: 97%
“…Cerebral autoregulation is impaired under most inhalation anesthetics 20,57 . However, vascular reactivity to Pco 2 is maintained reasonably well 23,58 . Halothane and isoflurane increase CBF and decrease oxygen consumption 59 .…”
Section: Use Of Appropriate Anesthesia and Maintenance Of Physiologicmentioning
confidence: 99%
“…In brain ischemia research, maintenance of Pao 2 is, of course, essential. Under physiological conditions CBF is dependent on Paco 2 23 . Maintenance of blood gas tensions at a constant level is therefore crucial.…”
Section: Use Of Appropriate Anesthesia and Maintenance Of Physiologicmentioning
confidence: 99%